PENGARUH MULTIMEDIA BERBASIS VIDEO INTERAKTIF TERHADAP MINAT & HASIL BELAJAR SISWA PADA PELAJARAN IPS KELAS VII SMPN 1 KEDUNGADEM BOJONEGORO - Choirun Nisa; Kusnul Khotimah; Hendri Prastiyono; Silvi Nur Afifah (STKIP Subang, 2026)
The advancement of digital technology necessitates learning innovations capable of enhancing students' interest and learning outcomes, particularly in Social Studies (IPS). This study aims to determine the impact of interactive video-based multimedia on the interest and learning outcomes of 7th-grade students at SMPN 1 Kedungadem, Bojonegoro. A quantitative approach was employed using a quasi-experimental design—specifically, the Nonequivalent Control Group Design. The study involved 56 students divided into an experimental class (VII A) and a control class (VII B). Data collection was conducted through pre-tests and post-tests, learning interest questionnaires, observation, and documentation. Data analysis utilized normality tests, homogeneity tests, independent sample t-tests, paired sample t-tests, and N-Gain tests, processed using SPSS version 25. The results indicate that interactive video-based multimedia had a positive and significant effect on students' interest and learning outcomes, with a significance value of 0.000 (< 0.05). The increase in interest and learning outcomes in the experimental class fell into the high category, whereas the control class fell into the medium category. Thus, interactive video-based multimedia is effective for use in Social Studies instruction to enhance student engagement and learning achievement.